Protein Bound Amino-Acids of Thevetia peruviania Leaves - Jain, S.K.; Yadav, R.N. (Asian Journal of Chemistry, 2010)
The amino-acids are the fundamental units of proteins structure. Protein bound amino-acids from the protein hydrolysate of defatted powdered leaves of T.peruviana have been separated and identified by uni and two dimentional paper chromatography. Determination and distribution of amino-acids were carried out by paper chromatography and price method.